Services, Comparative Advantage and Agglomeration of Economic Activity: A Ricardo-Marshall Model - Michael Pflüger; Takatoshi Tabuchi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The last century has witnessed dramatic changes in the world economy. The service (tertiary) sector, which at the beginning of the 20th century was of little importance relative to agriculture and manufacturing, has become the dominant sector today, accounting for 80% and more of value added in advanced countries and around 70% and of employment. Innovations in transport technologies and in information and communications technologies have radically reduced the costs of trading goods and have also made an increasing share of services tradeable. We propose a tractable micro-founded Ricardo-Marshall model to study the implications of the rise of the service sector and its interaction with international trade and factor mobility for the location of economic activity. Our model highlights a tension between nontradeable producer services which exert an agglomerative force and trade costs and comparative advantage in final goods and services which act as dispersion forces.
Keywords: F10; R12; R13; 330